The emergence of EU contract law exploring Europeanization - Miller, Lucinda (Oxford : Oxford University Press, 2011)
The emergence of an EU contract law is one of the most significant legal developments in Europe today. Exploring the evolution of the discipline, from the Sales Directive to the Common Frame of Reference, this book advances a framework for the further harmonization of contract law that embraces diversity and pluralism.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Contracts -- European Union countries